UKHUWAH ISLAMMIYAH DALAM PERSPEKTIF ALLAMA IQBAL - Putri - Silaturrahmi; Ibnu Khaldun - - (Dirosat : Journal of Islamic Studies, 2022)
Sir Muhammad Iqbal or better known as Allama Iqbal was an author, philosopher, lawyer, and politician in British India. He lived when the Mughal Dynasty collapsed, and Islam in South Asia was in chaos. At that time also, British troops managed to colonize some of the lands of South Asia. As a result the freedom of Muslims to worship is increasingly difficult, they are suppressed from all sides. This situation prompted Allama Iqbal to create a discourse known as the 'Pakistan Movement'. The goal is to liberate Muslims to be free from the confines of the colonialists and provide a solution to establish a new state for the Muslim community of South Asia to be able to practice Islam in peace. This scientific work was created with the aim of exploring the ideas of Ukhuwah Islammiyah in the perspective of Allama Iqbal and his contribution to taking part in the process of Islamization in society. This scientific work uses a literature study approach and historical analysis as a scientific approach to explore Allama Iqbal's thoughts on Ukhuwah Islammiyah. It is hoped that scientific work can be a reference material for intellectuals to explore insights about Ukhuwah Islammiyah.